Students in Twentieth-Century Britain and Ireland
XII, 328 p.
Keywords: This book explores the experiences and activities of students across the twentieth century and throughout the United Kingdom and Ireland. The daily experiences of students, their involvement in local communities, national political organisations and widespread cultural changes, are the main focus of this ground-breaking book. It takes students themselves as the subject of inquiry, exploring the fundamental importance of student activities within wider social and political changes and also how some of the key changes across the twentieth century have shaped and changed the make-up, experiences, and lives of students. This book charts the experiences of students throughout a period of unprecedented change as being a student in Britain and Ireland has gone from the endeavour of a small number of elite, mainly wealthy white men, to an important phase of life undertaken by the majority of young people.